Carotid artery assessment in dual-source photon-counting CT: impact of low-energy virtual monoenergetic imaging on image quality, vascular contrast and diagnostic assessability : computed tomography - Booz, Christian; Bucolo, Giuseppe M.; D’Angelo, Tommaso; Mazziotti, Silvio; Lanzafame, Ludovica R. M.; Yel, Ibrahim; Alizadeh, Leona S.; Gruenewald, Leon D.; Koch, Vitali; Martin, Simon S.; Dimitrova, Mirela; Goekduman, Aynur; et al. (La Radiologia medica, 2024)
Preliminary dual-energy CT studies have shown that low-energy virtual monoenergetic (VMI) + reconstructions can provide superior image quality compared to standard 120 kV CTA series. The purpose of this study is to evaluate the impact of low-energy VMI reconstructions on quantitative and qualitative image quality, vascular contrast, and diagnostic assessability of the carotid artery in patients undergoing photon-counting CTA examinations.
Online veröffentlicht: 17.September 2024
Gesehen am 14.01.2025